The Shipwreck of Their Hopes : THE BATTLES FOR CHATTANOOGA - Cozzens, Peter, 1957- (Book collections on Project MUSE., 1994)
In The Shipwreck of Their Hopes, Cozzens draws on his acclaimed storytelling skills and exhaustive research efforts to fully chronicle one of the South's most humiliating defeats. As in his earlier books, he brings to life the officers and enlisted men who fought the war.